A B C is a triangle with A C = 1 3 9 and B C = 1 7 8 . Points D and E are the midpoints of B C and A C respectively. Given that A D and B E are perpendicular to each other, what is the length of A B ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is a complete solution which also shows why the centroid of a triangle trisects the medians.
Note that there isn't a need to do various calculations, other than 5 1 7 8 2 + 1 3 9 2 = 1 0 2 0 1 .
Log in to reply
Comment on my solution.
Log in to reply
It is currently a B^2 feature to get a challenge master to specifically review your solution and give you feedback.
This Wikipedia entry on Median's Equal-area division contains a proof that the 3 medians of △ A B C will divide the triangle into 6 smaller triangles of equal area. In particular for us, we are interested in the result that 2 [ F B D ] = 2 [ F A E ] = [ F A B ] .
Since ∠ A F B = 9 0 ∘ , the usual area formula for triangle give us 2 F B ⋅ F D = 2 F A ⋅ F E = F A ⋅ F B , which simplifies to 2 F D = F A and 2 F E = F B .
Pythagorean theorem seals the deal for us with A C 2 = 4 A E 2 = 4 F A 2 + 4 F E 2 = 4 F A 2 + F B 2 ; B C 2 = 4 B D 2 = 4 F D 2 + 4 F B 2 = F A 2 + 4 F B 2 , and so A C 2 + B C 2 = 5 ( F A 2 + F B 2 ) = 5 A B 2 .
Lastly, we substitute in the values to get A C 2 = 5 1 3 9 2 + 1 7 8 2 = 1 0 1 .
Draw the picture. Assume that, B E and D F intersect at F . Also assume that, E F = x , and F D = y .
Also, A E = 2 A C = 2 1 3 9 and B D = 2 B C = 8 9 .
As we know that, by median formula. We obtain that :
B F = 2 ( E F ) = 2 x and A F = 2 ( F D ) = 2 y .
From the right △ B F D and △ A F E , we obtain :
x 2 + 4 y 2 = 4 1 3 9 2 … … ( 1 )
y 2 + 4 x 2 = 8 9 2 … … ( 2 )
Then, sum ( 1 ) and ( 2 ) , we obtain :
5 ( x 2 + y 2 ) = 4 5 1 0 0 5 ⟹ x 2 + y 2 = 4 1 0 2 0 1 .
Now, we see that the right △ A F B , then :
A F 2 + B F 2 = A B 2 4 x 2 + 4 y 2 = A B 2 4 ( 4 1 0 2 0 1 ) = A B 2 ⟹ A B 2 = 1 0 2 0 1 ⟹ A B = 1 0 1
First, we connect the points E and D . We let F be the intersection of AD and BE .
Given that AD and BE are perpendicular to each other, we will have the triangles AFE , BFD , AFB and EFD which are all right at F .
Since D and E are the midpoints of BC and AC respectively, it follows that DB and EA are equal to 89 and 2 1 3 9 respectively.
Considering the right triangles AFE and BFD , and applying the Pythagorean Theorem, we will have the following equations;
(1) A F 2 + E F 2 = 4 1 9 3 2 1
(2) B F 2 + D F 2 = 7921
Adding the equations (1) and (2), we will have;
(3) A F 2 + B F 2 + E F 2 + D F 2 = 4 5 1 0 0 5
Now, considering the right triangles AFB and EFD , and applying the Pythagorean Theorem, we will have the following equations;
(4) A F 2 + B F 2 = A B 2
(5) E F 2 + D F 2 = E D 2
Substituting (4) and (5) to (3), we will have the equation;
(6) A B 2 + E D 2 = 4 5 1 0 0 5
Given that D and E are the midpoints of BC and AC respectively, and applying the Mid-Segment Theorem, we can say that ED is 2 A B .
Replacing ED by 2 A B in (6), we will have the equation;
(7) A B 2 + 4 A B 2 = 4 5 1 0 0 5
Multiplying both sides of the equation by 4, we will have;
(8) 4 A B 2 + A B 2 = 51005
By addition, we will have;
(9) 5 A B 2 = 51005
Dividing both sides by 5, we will have;
(10) A B 2 = 10201
We extract the roots of both sides of the equations and considering only the positive solution (since measurements of length are positive) we will have;
AB = 101
The length of AB is 101.
Let the centroid be F. Note that F is the intersection of AD and BE.
We connect DE. Since CE/CA=CD/CB, and <ECD=<ACB, ECD and ACB are similar. Thus ED || AB and ED:AB=1:2. Note that <DEF=<FBA and <EDF=<FAB. Thus by AA similarity, EDF and BAF are similar.
Since ED:AB=1:2, EF/FB=1/2 and DF/FA=1/2. We let EF=x and DF=y. Thus FB=2x and FA=2y.
By the Pythagorean Theorem, BD^2=DF^2+FB^2=4x^2+y^2. BD^2=(178/2)^2=7921. AE^2=EF^2+FA^2=x^2+4y^2. EF^2=(139/2)^2=4380.25.
Thus we have the following equations: 4x^2+y^2=7921 x^2+4y^2=4380.25
Note that AB^2=(2x)^2+(2y)^2=4x^2+4y^2. Adding up the 2 equations we get 5x^2+5y^2=12751.25. Hence AB^2=4x^2+4y^2=(12751.25)/5*4=10201.
Hence AB=sqrt(10201)=101.
Since the two medians intersect at right angles, say at point F within the triangle, ( 1 ) three right triangles are formed: △ B F D , △ E F A , and △ A F B ; and ( 2 ) F is two-thirds of the way from every vertex of △ A B C . We can let x = F E and y = F D , so that B F = 2 x and A F = 2 y .
Using the Pythagorean Theorem on △ B F D , we have
( A ) 4 x 2 + y 2 = 8 9 2
From △ E F A , we have
( B ) x 2 + 4 y 2 = ( 2 1 3 9 ) 2
Also, from △ A F B , we have
( C ) 4 x 2 + 4 y 2 = A B 2
We don't need the exact values of x and y for this problem, since we are only asked to find the value of A B , which is equal to 4 x 2 + 4 y 2 . So it suffices to find the values of y 2 and x 2 .
Plugging in the expression for x 2 in terms of y 2 from ( B ) to ( A ) ( x 2 = ( 2 1 3 9 ) 2 − 4 y 2 ) , we can get y 2 = 7 6 0 , and 4 y 2 = 3 0 4 0 . Replacing y 2 by 7 6 0 in ( A ) , we get 4 x 2 = 7 1 6 1 . Thus, from ( C ) , A B = 3 0 4 0 + 7 1 6 1 = 1 0 2 0 1 , or A B = 1 0 1 .
Since E and D are midpoints of side AC and BD, therefore 2 E D = A B .
Let G be the intersection of line AD and BE.
By pythagoras theorem, we have:
G D 2 + G E 2 = E D 2
G E 2 + G A 2 = ( 2 1 3 9 ) 2 = 4 8 3 0 . 2 5
G A 2 + G B 2 = A B 2 = 4 E D 2
G B 2 + G D 2 = ( 2 1 7 8 ) 2 = 7 9 2 1
Combining first and third equation, we have the sum of squares of all sides is 5 E D 2 . Combining second and fourth equation, we have the sum of squares of all sides is 12751.25. Therefore, 5 E D 2 = 1 2 7 5 1 . 2 5 . So, E D = 5 0 . 5 and A B = 1 0 1 .
The property of a line joined by 2 mid points of a triangle's sides is that it will be parallel to the third line.
In this problem we are given that D and E are midpoints of B C and A C respectively, which according to the property, tell us that D E is parallel to A B
Also, let the intersection between B E and A D be F
According to similarity B A D E = C D C D = C A C E which gives us the value B A D E = 2 1
Consider the triangles A B F and D E F . A B is parallel to D E so ∠ F B A = ∠ F E D and ∠ F A B = ∠ F D E and we know that ∠ A F B = ∠ D F E = 9 0 ∘ so A B F is similar to D E F
so A B D E = B F E F = F A F D
Let F E = a and F D = b , so B F = 2 a and A F = 2 b
according to Pythagorean theorem, the following equations hold :
A F 2 + F E 2 = A E 2 → ( 2 b ) 2 + ( a ) 2 = 6 9 . 5 2 ...(1)
B F 2 + F D 2 = B D 2 → ( 2 a ) 2 + b 2 = 8 9 2 ...(2)
B F 2 + A F 2 = A B 2 → ( 2 a ) 2 + ( 2 b ) 2 = A B 2 ...(3)
(1)+(2)
5 a 2 + 5 b 2 = 1 2 7 5 1 . 2 5 .. multiply both sides by 0 . 8
4 a 2 + 4 b 2 = 1 0 2 0 1
Subtituting (3)
A B 2 = 1 0 2 0 1 → A B = 1 0 1
So the value of A B is 1 0 1
Let G be the intersection of A D with B E .
Since D and E are midpoints of B C and A C respectively, segments A D and B E are medians of the triangle, which in turn makes G be the centroid of triangle A B C .
For the sake of simplicity, let G D = a and G E = b .
Now, it is known that the centroid divides each median into parts in the ratio 2:1, which means A G = 2 G D = 2 a and B G = 2 G E = 2 b .
Since A D and B E are perpendicular to each other, we can use the Pythagorean Theorem on triangles A B G , B G D and A G E . We get from triangle A B G that A B 2 = B G 2 + A G 2 = 4 b 2 + 4 a 2 .
By the Pythagorean theorem on triangles B G D and A G E we obtain B D 2 = B G 2 + G D 2 = 4 b 2 + a 2 A E 2 = A G 2 + G E 2 = 4 a 2 + b 2 respectively. It's clear that B D = 2 B C = 8 9 and that A E = 2 A C = 6 9 . 5 . In other words, 8 9 2 = 4 b 2 + a 2 and 6 9 . 5 2 = 4 a 2 + b 2 . Adding these equations we get 6 9 . 5 2 + 8 9 2 = 5 ( a 2 + b 2 ) . Multiplying this last equation by 5 4 leads to
A B 2 = 4 ( a 2 + b 2 ) = ( 6 9 . 5 2 + 8 9 2 ) ( 5 4 ) = 1 0 2 0 1 . Therefore, A B = 1 0 1 .
LET AD AND BE INTERSECT AT O. SINCE AD AND BE ARE MEDIANS THEREFORE POINT O MUST BE THE CENTROID . AS WE KNOW THAT CENTROID DIVIDES THE MEDIAN IN THE
RATIO OF \frac {2}{1} , THEREFORE , LET AO=2X, OD =X BO=2Y,OE=Y
SINCE AD AND BE ARE PERPENDICULAR TO EACH OTHER THEREFORE,
AO^2+OE^2=AE^2 AND BO^2+OD^2=BD^2
SO, 4X^2+Y^2=(69.5)^2 AND 4Y^2+X^2=89^2
ADDING THE TWOEQUATIONS , WE GET 5(X^2+Y^2)=\frac {51005}{4} SO, 4(X^2+Y^2)=\frac {51005}{5} SO,AB^2=10201 AND HENCE AB =101.
Let A D and B E intersect at G , which is the centroid of the triangle. We know that A G = 2 G D and B G = 2 G E .
Applying the Pythagorean theorem on triangles B G D and A G E , we get that
4 G D 2 + G E 2 = ( 2 A C ) 2 , 4 G E 2 + G D 2 = ( 2 B C ) 2 .
Hence, A B 2 = 4 G D 2 + 4 G E 2 = 5 4 [ ( 2 A C ) 2 + ( 2 B C ) 2 ] = 1 0 2 0 1 . Thus, A B = 1 0 1 .
. Let F is the intersection point of AD and BE. Triangle EDC is similar to ABC (length ratio 1:2). Let EF=a, and FD=b. a2 + 4b2 = (139/2)2, b2 + 4a2 = (178/2)2, So a2 = 1790.25, b2 = 760, AB2 = 4a2 + 4b2 = 10201, AB = 101.
The formula for this question is square root (a^2+b^2)/2=squreroot (10201)=101.
Let the point where A D and B E intersect be F.
Let the length A F be x and B F be y .
Since each of the medians divide one another in the ratio 1:2, we can write D F as 2 x and E F as 2 y .
By Pythagoras' Theorem, we have, after simplifying:
4 x 2 + y 2 = 1 3 9 2 (Equation 1 from triangle A F E )
x 2 + 4 y 2 = 1 7 8 2 (Equation 2 from triangle B F D )
Adding the two equations together,
5 x 2 + 5 y 2 = 5 1 0 0 5
x 2 + y 2 = 1 0 2 0 1
Since A B , the required length, is the hypotenuse of right-angled triangle A B F with edges of length A F = x and B F = y , Pythagoras' Theorem gives us the final answer:
x 2 + y 2 = 1 0 1
I used a coordinate system with the intersection of BE and AD as the origin, and E, D on the x-axis and y-axis, respectively. The coordinates of the various points may now be written as A ( 0 , − a ) ; B ( − b , 0 ) ; D ( 0 , d ) ; E ( e , 0 ) , and from the fact that D and E are midpoints, C ( b , 2 d ) = ( 2 e , a ) , so that d = 2 a , e = 2 b . The given lengths show that a 2 + e 2 = 4 1 ⋅ 1 3 9 2 , b 2 + d 2 = 4 1 ⋅ 1 7 8 2 ; we must find the square root of a 2 + b 2 = ( a 2 + e 2 + b 2 + d 2 ) − ( b 2 + d 2 ) = 4 1 ( 1 3 9 2 + 1 7 8 2 ) − 4 1 ( a 2 + b 2 ) , a 2 + b 2 = 5 1 3 9 2 + 1 7 8 2 = 1 0 2 0 1 , from which we find A B = a 2 + b 2 = 1 0 1 .
Problem Loading...
Note Loading...
Set Loading...
Connect points D and E . Triangles D E C and B A C are similar by S A S , so D E is parallel to B A . Let the intersection of A D and B E be F . Triangles D F E and A F B are similar by A A and the similarity ratio is 2 1 because D E is 2 1 of B A . By the Pythagorean theorem, D F 2 + ( 2 F E ) 2 = 8 9 2 , F E 2 + ( 2 D F ) 2 = 6 9 . 5 2 , and D F 2 + F E 2 = D E 2 . Adding the first two equations and dividing by 5 gives D F 2 + F E 2 = D E 2 = 2 5 5 0 . 2 5 . So D E = 5 0 . 5 and B A = 1 0 1 .